(untitled) (Numerus academy review, 2026)
This study aimed to highlight the importance of employing the knowledge economy in the banking industry, by addressing its concept, characteristics and employment in the banking industry, through electronic payment by its means and channels, while addressing Algeria’s efforts in this field. The study concluded that employing the knowledge economy in the banking industry has become more than a necessity, especially in light of the exceptional health conditions the world is witnessing, which require more social distancing as a result of the spread of the Corona pandemic, because technology enables access to services remotely.